(untitled) (Transactions of the Association of European Schools of Planning, 2021)
This issue (5.2) of Transactions of AESOP brings together a selection of papers which address current themes and issues in planning education. Two of the papers reflect on the experience of teaching modules submitted to recent rounds of the AESOP Excellence in Teaching Award (ETA), one reports on an experience of internationalisation in planning education, and one is an invited paper by Andrea Frank the present Chair of the AESOP ETA Committee. They all provide original and insightful contributions addressing key themes in contemporary planning education including, the impacts of the COVID-19 pandemic, new technologies and modes of teaching delivery, the teaching of landscape in planning programmes, and, the internationalisation of planning cohorts and curricula.